The permanent training of nurses and their insertion in intensive care at the university hospital (Research, Society and Development, 2020)
Considering the presence of novice nurses in the Intensive Care, requesting productivity and good performance; this study aims to describe how the insertion of a nurse for the Intensive Care Unit occurred; to identify the aspects that have influenced the permanent training in the context of his/her admission and post-admission at the Intensive Care Unit. 20 semistrucured interviews were conducted, worked on analysis content and Schon´s toughts. The categories lifted: the nurse in the course of a critical-reflexive learning; understanding the performance of another nurse; and developing his/her artistic professional talent as a leader in nursing. The nurses sought to bring back knowledge, used strategies for learning; observed the veteran´s performance; the embracement was a factor that eased the learning; infrastructure lacks related to the university hospital did not favored the learning; to be a leader and a beginner was a challenge faced by the nurses.